A Comprehensive Observational Coding Scheme for Analyzing Instrumental, Affective, and Relational Communication in Health Care Contexts - Siminoff, Laura A.; Step, Mary M. (Journal of health communication, 2011)
Many observational coding schemes have been offered to measure communication in health care settings. These schemes fall short of capturing multiple functions of communication among providers, patients, and other participants. After a brief review of observational communication coding, the authors present a comprehensive scheme for coding communication that is (a) grounded in communication theory, (b) accounts for instrumental and relational communication, and (c) captures important contextual features with tailored coding templates: the Siminoff Communication Content & Affect Program (SCCAP). To test SCCAP reliability and validity, the authors coded data from two communication studies. The SCCAP provided reliable measurement of communication variables including tailored content areas and observer ratings of speaker immediacy, affiliation, confirmation, and disconfirmation behaviors.